Tumoral calcinosis: a case report - Özkan, İlhan and Türeli, Cem and Çullu, Emre and Karaman, Can and Şendur, Faruk and Alparslan, Bülent (The Turkish Journal of Pediatrics, 1999)
Tumoral calcinosis is a rare disorder with the calcified masses in subcutaneous tissues. We report herein a nine-year-old girl, in whom the calcified lesions bilaterally involved the soft tissues in the anterior part of the knee joint. Serum calcium and phosphorus levels were in normal ranges and there was no family history. Surgical excision was performed and recurrence was not observed in early follow-up. Review of the literature shows that only clinical and radiological appearance of tumoral calcinosis are generally agreed while its epidemiology, etiology and treatment are still under discussion.